Multicentric evaluation of model for end-stage liver disease-based allocation and survival after liver transplantation in Germany: limitations of the ‘sickest first’-concept - Weismüller, Tobias Johannes; Fikatas, Panagiotis; Schmidt, Jan; Barreiros, Ana P.; Otto, Gerd; Beckebaum, Susanne; Paul, Andreas; Scherer, Markus N.; Schmidt, Hartmut H.; Schlitt, Hans J.; Neuhaus, Peter; Klempnauer, Jürgen; et al. (Transplant international, 2011)
Since the introduction of model for end-stage liver disease (MELD) in 2006, post-orthotopic liver transplantation (OLT) survival in Germany has declined. The aim of this study was to evaluate risk factors and prognostic scores for outcome. All adult OLT recipients in seven German transplant centers after MELD implementation (December 2006-December 2007) were included. Recipient data were analyzed for their influence on 1-year outcome. A total of 462 patients (mean calculated MELD = 20.5, follow-up: 1 year) were transplanted for alcoholic cirrhosis (33.1%), hepatocellular carcinoma (26.6%), Hepatitis-C (17.1%), Hepatitis-B (9.5%), primary sclerosing cholangitis (5.6%) and late graft-failure after first OLT before December 2006 (8.7%). 1-year patient survival was 75.8% (graft survival 71.2%) correlating with MELD parameters and serum choline esterase. MELD score >30 [odds ratio (OR) = 4.17, confidence interval: 2.57-6.78, 12-month survival = 52.6%, c-statistic = 0.669], hyponatremia (OR = 2.07), and pre-OLT hemodialysis (OR = 2.35) were the main death risk factors. In alcoholic cirrhosis (n = 153, mean MELD = 21.1) and hepatocellular carcinoma (n = 123, mean MELD = 13.5), serum bilirubin and the survival after liver transplantation score were independent outcome parameters, respectively. MELD >30 currently represents a major risk factor for outcome. Risk factors differ in individual patient subgroups. In the current German practice of organ allocation to sicker patients, outcome prediction should be considered to prevent results below acceptable standards.